Forensic Art and Illustration. - Taylor, Karen T. (CRC Press, 2000)
This text proceeds through explanations of facial anatomy, practical methodologies and techniques and case examples in forensic art. It uses illustrations and photographs to depict art methods used in identifying and locating crime victims and criminal offenders.